Vibromyographic recording from human muscles with known fibre composition differences. Issue 1 (March 1996) - Mealing, D; Long, G; McCarthy, P W
Abstract : OBJECTIVE–To determine the relation between the vibromyographic (VMG) frequency characteristics and fibre composition in postural and non-postural human muscle undergoing a standardised voluntary contraction. METHODS–Two human muscles with different fibre compositions [soleus: postural, mainly type I (slow) fibres; biceps brachii: non-postural, mixed type I and II (fast) fibres] were recorded from 18 healthy males isometrically contracting at 50% of their maximum voluntary contraction (MVC). Muscle vibrations were recorded using a contact microphone and the frequency content of the signals calculated using fast fourier transform algorithms. RESULTS–The non-postural biceps brachii showed predominantly bimodal power spectra with significantly increased power in the 10-30 Hz bands (P < 0.01), as compared with soleus recordings which tended to be unimodal, with the majority of power below 10 Hz. CONCLUSIONS–Muscles with a large proportion of type I fibres generate VMG signals which contain an increased percentage of low frequencies as compared to muscles with a mixed population of type I and type II fibres. The VMG appears to be generated, in part at least, by the mechanical twitching of motor units within the muscle; frequency domain analysis of this signal may provide a non-invasive measure of muscle fibre composition.